Virus Screening Of Cultured Carp And Tilapia Species And The Virus Sensitivity Of Cell Cultures From Indigenous Fish Species - Juan Deanon, Albaladejo (1994)

(untitled)
Three virus particles were isolated in vitro and tentatively classified into three groupings , namely Herpesviridae, Birnaviridae and Iridoviridae . Virus groupings were based on the ultrastructural morphology and cytopathology observed . Distinct virus-like cytopathic effects were noted on four established fish cell lines viz . CHSE-214 , GCK-84 , EPC and TmB , utilized in the study . The virus - like particles , from pelleted infected cell cultures and clarified cell culture supernatant, were visualized under transmission electron microscopy .Virus titration utilizing BB cells for the Birnavirus - like isolate achieved a mean titre of 7.40 X 105 TC ID50/ml. Relatively high virus titres were also recorded from the other two isolants , with a mean virus titres of 7.16 X 105 TC ID50/ml for Herpesvirus - like and 6.4 6 'x 105 TCID50/ml for Iridovirus-like .